The relationship of some physical variables and performance angles to the strength of the straight serve in tennis - Zainab Shakir; dr. Widad Kadhum (physical education and sport sciences college for women/ Baghdad University, 2021)
The problem of the research in determining the appropriate angles in the strength of serve for tennis age (14-16) year according to the specific biomechanical conditions, and the extent of the relationship of each variable of the physical variables in the successful performance of the skill of serve, and achieving the strength of transmission for tennis age (14-16) year, and it is one of the biomechanical principles that can be used in evaluating the angles of body parts. age (14-16) year tennis players. The aim of the research is to identify the percentage of the contribution of some physical variables of the straight serve for tennis juniors, and the percentage of the contribution of some corners of the body to the strength of serve for the tennis age (14-16) year (18) players. The two researchers reached a number of results, the most important of which are: There is a statistically significant correlation between some physical abilities and body angles with the straight serve for tennis players. The lower the angles (elbow, shoulder, knee for the front leg) at the moment of hitting the tennis ball, the stronger the serve will be. Correlation relationship with some biomechanical variables, because the skill of serve requires the strength of the striking arm during the performance of the straight serve